Comparison of alaryngeal voice and speech - Globlek, Dubravka (Array, 2004)
The aim of the research was to compare voice and speech in three groups of alaryngeal speakers: (1) esophageal speakers ; (2) patients with electroacoustical aids ; and (3) patients with voice prosthesis. Results demonstrated the advantage of voice with prosthesis.